Genetic Mapping of Head Size Related Traits in Common Carp (Cyprinus carpio) - Chen, Lin; Peng, Wenzhu; Kong, Shengnan; Pu, Fei; Chen, Baohua; Zhou, Zhixiong; Feng, Jianxin; Li, Xuejun; Xu, Peng (Frontiers in Genetics, 2018)
Head size is important economic trait for many aquaculture fish which is directly linked to their carcass yield. The genetic basis of head size trait remains unclear in many widely-cultured fish species. Common carp (Cyprinus carpio) is one of the most widely studied fish due to its importance on both economic and environmental aspects. In this study, we performed genome-wide association study using 433 Yellow River carp individuals from multiple families to identify loci and genes potentially associated with head size related traits including head length (HL), head length/body length ratio (HBR), eye diameter (ED) and eye cross (EC). QTL mapping was utilized to filter the effects of population stratification and improve power for the candidate identification in the largest surveyed family with a published genetic linkage map. Twelve SNPs showed significant for head size traits in GWAS and 18 QTLs were identified in QTL mapping. Our study combining both GWAS and QTL mapping could compensate the deficiency from each other and advance our understanding of head size traits in common carp. To acquire a better understanding of the correlation between head size and body growth, we also performed comparisons between QTLs of head size traits and growth-related traits. Candidate genes underlying head size traits were identified surrounding the significant SNPs, including parv, srpk2, fsrp5, igf1, igf3, grb10, igf1r, notch2, sfrp2. Many of these genes have been identified with potential functions on bone formation and growth. Igf1 was a putative gene associated with both head size and body growth in Yellow River carp. The teleost-specific igf3 is a candidate head size related gene, related to both head length and head length/body length ratio. Our study also indicated the importance of Igf signaling pathway for both growth and head size determination in common carp, which could be potentially used in future selective breeding in common carp as well as other species.